2020
DOI: 10.2217/nnm-2019-0371
|View full text |Cite
|
Sign up to set email alerts
|

Novel Intracellular Antibiotic Delivery System Against Staphylococcus Aureus : Cloxacillin-Loaded Poly( D , L -Lactide-Co-Glycolide) Acid Nanoparticles

Abstract: Aim: First, to compare in vitro minimum inhibitory concentrations (MIC) of free cloxacillin and cloxacillin-containing nanoparticles (NP) against methicillin-susceptible (MSSA) and resistant Staphylococcus aureus (MRSA) and second, to assess NP antimicrobial activity against intracellular S. aureus. Methods: Poly(d,l-lactide-co-glycolide) acid (PLGA)-NP were loaded with cloxacillin and physico-chemically characterized. MICs were determined for reference strains Newman-(MSSA) and USA300-(MRSA). Murine alveolar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…For instance, PLGA nanoparticles loaded with curcumin showed greater antibacterial activity on different bacterial strains than free curcumin [ 26 ]. Additionally, Lacoma et al reported significant antimicrobial activity of cloxacillin-loaded PLGA nanoparticles compared to free cloxacillin against Staphylococcus aureus [ 27 ]. Cardamom oil-loaded chitosan nanoparticles were found to exhibit excellent antimicrobial potential against extended-spectrum lactamase-producing Escherichia coli and methicillin-resistant Staphylococcus aureus [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, PLGA nanoparticles loaded with curcumin showed greater antibacterial activity on different bacterial strains than free curcumin [ 26 ]. Additionally, Lacoma et al reported significant antimicrobial activity of cloxacillin-loaded PLGA nanoparticles compared to free cloxacillin against Staphylococcus aureus [ 27 ]. Cardamom oil-loaded chitosan nanoparticles were found to exhibit excellent antimicrobial potential against extended-spectrum lactamase-producing Escherichia coli and methicillin-resistant Staphylococcus aureus [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the phenolic hydroxy group of thymol enhanced its hydrophilic property, leading to inhibition of bacterial growth and even killing them [6]. Improved [27]. Cardamom oil-loaded chitosan nanoparticles were found to exhibit excellent antimicrobial potential against extended-spectrum lactamase-producing Escherichia coli and methicillin-resistant Staphylococcus aureus [28].…”
Section: Discussionmentioning
confidence: 99%
“…The MIC and MBC values of pAgNCs@PLGA were found to be lower compared to pAgNCs alone, which indicates that pAgNCs have greater antibacterial potency when loaded in PLGA. The reason may be due to better delivery of pAgNCs in its site of action and the improvement of antibacterial activity due to encapsulation in PLGA [39,50] . This finding could also be attributed to the degradation of lactic acid which has a weak lipophilic nature and its passage through the cell membrane, releasing protons, acidifying the cytoplasm, causing homeostatic imbalance and contributing to the antibacterial effect of pAgNCs [51] .…”
Section: Resultsmentioning
confidence: 99%
“…The reason may be due to better delivery of pAgNCs in its site of action and the improvement of antibacterial activity due to encapsulation in PLGA. [39,50] This finding could also be attributed to the degradation of lactic acid which has a weak lipophilic nature and its passage through the cell membrane, releasing protons, acidifying the cytoplasm, causing homeostatic imbalance and contributing to the antibacterial effect of pAgNCs. [51] SEM images of the bacteria exposed to pAgNCs and composites are shown in Figure 5(A-F).…”
Section: Antibacterial Studiesmentioning
confidence: 99%
“…Encapsulation of antimicrobial drugs into NPs can improve muco-adhesion and penetration of cell membranes, as well as intracellular delivery of antibiotics to combat various bacteria (e.g. Staphylococcus aureus [18][19][20], Escherichia coli [21], Mycobacterium abscessus [19], Klebsiella pneumonia [22], Chlamydia trachomatis [23] and Mycobacterium tuberculosis [24,25]), including those that are classified as extracellular pathogens but also show intracellular residence in host cells. Despite its promise as an alternative avenue for combating bacteria, understanding the interaction between NP and cells and management of nanomaterial toxicity often associated with inorganic nanomaterials remain as an important consideration for nanomaterial-based therapeutics [26].…”
Section: Introductionmentioning
confidence: 99%